1981
DOI: 10.1038/bjc.1981.52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal dysfunction in dogs on the disposition and marrow toxicity of melphalan

Abstract: Summary.-The effect of renal failure on melphalan pharmacology and toxicity has been poorly understood. Such information is of interest because melphalan is the most commonly used anticancer drug in the treatment of multiple myeloma, which is frequently associated with renal failure. We have studied the disposition and marrow toxicity of parenteral melphalan in dogs before and after induction of renal failure with subtotal nephrectomy. The surgical procedure decreased the creatinine clearance by an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…In fact, antineoplastic drugs have a narrow therapeutic index, so that major toxicity can occur in patients with impaired renal function, owing to an increase in dose intensity that is difficult to predict. In this regard, an early study conducted in dogs with renal failure 6 demonstrated an increased hematological toxicity of melphalan related to a longer terminal half-life of the drug. A similar finding has been reported in MM patients receiving oral melphalan, 7 while in another study, the frequency of severe myelosuppression induced by oral melphalan was not related to renal function.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, antineoplastic drugs have a narrow therapeutic index, so that major toxicity can occur in patients with impaired renal function, owing to an increase in dose intensity that is difficult to predict. In this regard, an early study conducted in dogs with renal failure 6 demonstrated an increased hematological toxicity of melphalan related to a longer terminal half-life of the drug. A similar finding has been reported in MM patients receiving oral melphalan, 7 while in another study, the frequency of severe myelosuppression induced by oral melphalan was not related to renal function.…”
Section: Introductionmentioning
confidence: 99%
“…This rather surprising grade of myelosuppression is probably due to the use of melphalan intravenously after cisplatinum in the period (day 2) when there is functional tubular damage caused by the latter. Melphalan is highly myelotoxic in the presence of renal function impairment [15], and in fact the combination caused leukopenia and especially thrombocytope nia (median nadir values between the 4th and 5th cycles), which were ameliorated by dropping the hexamethylmelamine from the regimen. A relatively short treatment duration of 4-6 months might also help to restrict the neurotoxicity caused by cis-platinum and possibly enhanced by hexamethylmelamine, which has been described elsewhere [16] by our group.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Melphalan undergoes rapid chemical degradation and has little, if any, active metabolism. 28,29 Early studies revealed increased melphalan-induced myelosuppression in nephrectomized dogs, 30 and renal insufficiency significantly increased melphalan-induced myelosuppression in patients with MM. 31 Reduction of the intravenous dose of melphalan to 50% in patients with elevated BUN reduced the frequency of these complications to levels that were not significantly different from those observed in patients with normal renal function.…”
Section: Renal Impairmentmentioning
confidence: 98%